Profile of Geohelminth Eggs, Cysts, and Oocysts of Protozoans Contaminating the Soils of Ten Primary Schools in Dschang, West Cameroon - Vanessa Rosine Nkouayep; Blandine Ngatou Tchakounté; Josué Wabo Poné (Journal of Parasitology Research)
Helminthiasis and protozoans infections have been recognized as an important public health problem. The aim of the present study was to screen soil samples collected from 10 primary schools in the city of Dschang for the presence of soil-transmitted helminth eggs, cysts, and oocysts of protozoans. A total of 400 soil samples were collected around latrines, at playgrounds, and behind classrooms in each school. These samples were examined using the sucrose flotation method. From the result obtained, an overall contamination rate of 7.75% was observed. Five genera of nematodes (Ascaris, Trichuris, Capillaria, Cooperia, and hookworms) were identified, while neither cysts nor oocysts of protozoans were detected. The contamination rate and the number of species found were significantly different in wet season as compared to the dry season. During the rainy season, this rate was 12.5% with all the parasitic stages identified, while, in the dry season, the soil contamination rate was 3% with the presence of only two genera (Ascaris and Trichuris). This suggests that parasite infection may occur mainly in rainy season rather than in the dry season. The most common eggs were those of Ascaris with 2% and 5% contamination rates in the dry and rainy seasons, respectively. Also, the soils around latrines were more contaminated (11.9%) as compared to those collected behind classrooms (7.5%) and those at playground (2.5%). It was concluded that the pupils of these schools may have played a major role in the contamination of their environment. Thus, sanitary education, enforcement of basic rules of hygiene, and deworming remain a necessity in the entire population of the study area in general and in the schools in particular in order to prevent helminth infections and to ensure effective environmental health.